Molecular characterization of black pepper (piper nigrum L.) genotypes for drought tolerance - Pallavi V (Department of plant biotechnology, College of horticulture, 2015)
Black pepper (Piper nigrum L) the “King of spices” and a perennial climber belonging to the family Piperaceae, is known for its quality and it fetches premium price in the international market. Ninety per cent of the area under black pepper is rainfed. As India is the primary centre of diversity of black pepper, the indigenous genetic resources are reservoirs of useful genes for plant improvement programmes. Black pepper is grown mainly in Kerala, where water deficit during off season viz., December-May is a common feature. To avoid reduction in yield during water stress condition, cultivation of drought tolerant varieties is essential (Rajagopal and Balasimha, 1994).The present study on “Molecular characterization of black pepper (Piper nigrum L.) genotypes for drought tolerance” was under taken at the Centre for Plant Biotechnology and Molecular Biology, College of Horticulture, Vellanikkara during the period 2013-2015 with the objective of screening the selected black pepper genotypes for drought tolerance and identifying differentially expressed, up regulated, down regulated genes by transcriptome analysis. The genotypes PRS 64(Angamaly), PRS 155(wild type), PRS 115(Panniyur-5), PRS 149(wild type), PRS 156, PRS 160(Hybrid), PRS 161(Hybrid), PRS 153(Panniyur-8), PRS 44(Panniyur-1) and Karimunda were selected for the study. Water stress was imposed on all the genotypes for 15 days continuously on six month old rooted cuttings and observations on relative water content and membrane integrity were taken at 5 days interval. Days taken for wilting were also noted. The genotypes showed different responses to physiological parameters such as relative water content, membrane integrity and days taken for wilting. Relative water content and membrane integrity were reduced with increasing stress intensity. Relative water content was positively correlated with membrane integrity and negatively correlated with stress intensity. The PRS-64(Angamaly) showed highest relative water content and membrane integrity which was on par with PRS- 115(Panniyur-5), PRS-160, PRS-153(Panniyur-8). The lowest relative content and membrane integrity was observed in PRS-44(Panniyur-1) which was on par with Karimunda. The number of days taken for wilting varies between genotypes. Angamaly took 23 days to wilt which was on par with Panniyur-8. Panniyur-1 took 13 days to wilt which was on par with PRS-156. PRS-64 identified as most drought tolerant genotype and PRS-44 identified as susceptible genotype The mechanisms for abiotic stress tolerance are based on activation and regulation of specific set of stress-related genes which are involved in signalling, transcriptional control, and protection of membrane proteins. The technique used to analyse the transcriptome was differential display-RTPCR which allows extensive analysis of gene expression among several cell populations (Sturtevant, 2000). The gene expression analysis requires good quality RNA which was isolated by Trizol reagent method with utmost care to prevent its degradation by nucleases. One μg of total RNA from the two treatments were taken for DD-RT-PCR analysis. The first strand cDNA was synthesized from the above RNA samples using HT11G (AAGCTTTTTTTTTTTG). Each first strand cDNA was used for the second amplification with 8 different arbitrary primers. The PCR product was resolved in 6 per cent denaturing urea polyacrylamide gels and visualized after silver staining. The gel was dried overnight for the elution and further analysis. The up regulated, down regulated and differentially expressed cDNA fragments were retrieved from the gel and reamplified with the same set of primers as in the initial DD-RT-PCR reaction and analysed electrophoretically. The agarose gel electrophoresis showed that the transcript derived fragments (TDFs) obtained were relatively short (400-900bp). TDFs were cloned using pGEMT vector. The clones were sequenced at Sci Genome, Cochin. The sequence data obtained were analysed by in silico tools. The sequence from differentially expressed TDFs showed homology to copper containing amine oxidases which have a broader range of functions, including cell differentiation and growth, wound healing, detoxification and cell signalling. It contributes to terminal polyamines oxidation in peroxisomes. Polyamines are involved in different physiological processes such as growth development and response to abiotic stress. The other major genes identified were NADH dehydrogenase, heat shock proteins, ribosomal RNA gene, protein kinase which is all operating in major signal transduction pathways.